An Efficient and Simplified Data Hiding Technique Based on 2's Complement - Tzu Chuen Lu; Chun Ya Tseng; Chang Mu Chen; Hui Shih Leng; Ying Hsuan Huang (2014 Tenth International Conference on Intelligent Information Hiding and Multimedia Signal Processing, 2014)
In recent years, several data hiding techniques have been developed. Hsiao and Chang proposed a data hiding scheme in 2011. This approach utilizes just noticeable distortion (JND) techniques to determine whether a pixel can be included in hidden information based on its value, but the calculation procedure is very complex. Therefore, our research seeks to improve Hsiao and Chang's method through the use of an alternate technique to replace JND techniques, specifically through the use of the 2's complement to embed hidden information in an image. Our experimental results demonstrate that our approach achieves high quality and hidden capacity without the need for JND techniques and their associated computational cost.